Acrylamide Induces Antiapoptotic Autophagy and Apoptosis by Activating PERK Pathway in SH-SY5Y Cells - Yiqi Wang; Ying Liu; Xing Zhang; Yang Jiao; Lian Duan; Ruijie Cheng; Ning Yang; Hong Yan (Toxics)
Acrylamide (ACR) is a commonly used organic compound that exhibits evident neurotoxicity in humans. Our previous studies showed that the mechanisms of ACR-caused neurotoxicity included apoptosis, PERK-mediated endoplasmic reticulum stress, and autophagy, but the relationships among them were still unclear. This paper investigated the relationships among apoptosis, autophagy, and the PERK pathway to demonstrate the mechanism of ACR neurotoxicity further. Different doses of ACR were set to value ACR toxicity. Then, a PERK inhibitor and autophagy inhibitor, GSK2606414 and 3-methyladenine (3-MA), were used separately to inhibit the PERK pathway and autophagy activation in SH-SY5Y cells under ACR treatment. With the increase of ACR dose, the apoptotic rate increased in a dose-dependent manner. After the inhibition of the PERK pathway, the activated apoptosis and autophagosome accumulation caused by ACR were alleviated. Under 3-MA and ACR treatment, the autophagy inhibition deteriorated apoptosis in SH-SY5Y cells but had no significant effect on ACR-induced PERK pathway activation; thus, PERK pathway-induced autophagy had an antiapoptotic role in this condition. This paper provides an experimental basis for exploring potential molecular targets to prevent and control ACR toxicity.